IMPLEMENTASI MANAJEMEN KINERJA SUMBER DAYA MANUSIA DALAM MENINGKATKAN KUALITAS PELAYANAN - Rahayu, Rita Putri; Sunaryo, Sunaryo (Jurnal Kewirausahaan dan Inovasi, 2022)
The objective of this research is to identify the implementation of human resource performance management in increasing the service quality of the Islamic-compliant business unit of PT Bank Sinarmas in the branch office of Malang. This descriptive qualitative research uses primary and secondary data, which were harvested through interviews and documentation and validated using source triangulation, method triangulation, and theory triangulation. The research subjects are four employees as key informants and three customers as main informants. The data analysis was performed using data reduction, data presentation, and conclusion drawing. This research finds that the said business unit has well organized the four stages of performance management, i.e. planning/directing, monitoring, review evaluation/appraising, and reward & developing. The unit has also run the five quality of service, i.e. reliability, responsiveness, assurance, empathy, and physical evidence. However, setbacks are still found in empathy and physical evidence, where customers were not satisfied with the unit’s telephone service and  ATM distribution.